Tinjauan Hukum Islam Terhadap Praktik Kerjasama Dalam Earn Money Maker Application (Studi Kasus Aplikasi Capcut) - Zami, M. Taufiq Zam; Noftiana, Faza (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
The practice of collaboration in the Earn Money Maker Application in the Capcut application is a collaboration carried out between the leader agency and the Capcut creator in the Capcut agency program. The problem in this research is how the cooperative practices in the Earn Money Maker Application in the Capcut application are carried out by the leaders and creators. Then the aim of this research is how Islamic law reviews the practice of cooperation in the Earn Money Maker Application in the Capcut application. The type of research used is field research with qualitative descriptive methods and using an empirical juridical approach. Data collection techniques using observation, interviews and documentation are then analyzed using qualitative methods. The results of this research are a review of Islamic law regarding cooperation practices in the Earn Money Making Application in the Capcut application, including cooperation in the form of syirkah abdan. There are several things that happen that are not in accordance with the pillars and requirements of syirkah abdan. Namely aqidain (contracting parties) who do not meet the requirements.